Peningkatan Hasil Belajar Siswa Kelas IV melalui Model Contextual Teaching And Learning Berbantuan E-Modul Berbasis Budaya Pati - SIYAMSARI, DESY; RAHAYU, RATRI; KIRONORATRI, LINTANG (Universitas Muria Kudus, 2023)
This study aims to examine the increase in knowledge learning outcomes of fourth grade elementary school students using the CTL model assisted by Pati culture-based e-modules. This type of research is a quantitative experiment, pre-experimental research design, pretest-posttest design model. Non-test and test data collection techniques. The data analysis technique uses the initial data analysis in the form of a normality test, while the final data analysis is in the form of quantitative descriptive statistical analysis and hypothesis testing. Based on the results of testing the n-gain hypothesis, it is proven that there is an increase in knowledge learning outcomes with the starch-based e-module assisted CTL model of 0.55 medium criterion interpretation. So it was concluded in this study that there had been an increase in the knowledge learning outcomes of class IV students with the CTL model assisted by e-module based on starch culture.